2010
DOI: 10.3168/jds.2009-2451
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wide swathing on wilting times and nutritive value of alfalfa haylage

Abstract: On 3 consecutive cuttings, alfalfa from a single field was mowed with a John Deere 946 mower-conditioner (4-m cut width; Moline, IL) to leave narrow swaths (NS) ranging from 1.2 to 1.52 m wide (30-37% of cutter bar width) and wide swaths (WS) ranging from 2.44 to 2.74 m wide (62-67% of cutter bar width). Samples were collected from windrows and dry matter (DM) was monitored during wilting until a target of 43 to 45% DM was obtained. Forage from random windrows (n=4-6) was harvested by hand, chopped through a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Wilting alfalfa in wide swaths reduced the drying time needed to reach 350 g DM kg −1 FM by 9 h (−28%) under slow wilting (i.e., the spring of 2008) and by 2 h (−18%) under fast drying conditions (i.e., the summer and autumn of 2008, and spring and summer of 2009). This result concurs with Kung et al (2010) who reported that the drying time to reach 350 g DM kg −1 FM was reduced by 3 to 4 h (11 to 50%) in wide swaths, resulting in greater NSC concentration compared with narrow swaths. Shinners and Herzmann (2006) with alfalfa and Wilkinson et al (1999) with perennial ryegrass reported similar results.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Wilting alfalfa in wide swaths reduced the drying time needed to reach 350 g DM kg −1 FM by 9 h (−28%) under slow wilting (i.e., the spring of 2008) and by 2 h (−18%) under fast drying conditions (i.e., the summer and autumn of 2008, and spring and summer of 2009). This result concurs with Kung et al (2010) who reported that the drying time to reach 350 g DM kg −1 FM was reduced by 3 to 4 h (11 to 50%) in wide swaths, resulting in greater NSC concentration compared with narrow swaths. Shinners and Herzmann (2006) with alfalfa and Wilkinson et al (1999) with perennial ryegrass reported similar results.…”
Section: Resultssupporting
confidence: 92%
“…Drying phases for cut plants include: (i) rapid initial drying with water loss mostly by evapotranspiration through open stomata, (ii) a longer drying period with water loss through stem and leaf cuticle, and (iii) slow loss of the remaining tightly‐held water (Demarquilly, 1987; Moser, 1995). Allowing the forage to dry in wide swaths rather than in narrow swaths accelerates all three phases (Rotz, 1995; Wilkinson et al, 1999; Kung et al, 2010). Wilting conditions affect forage NSC concentration because metabolism remains active after cutting and depletes carbon reserves until dehydration reaches the point where respiration is impaired.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Buffering capacity tended to be greater for forages receiving no slurry compared with slurry-applied forages (383 vs. 364 mEq/kg; P = 0.063), and for ideal compared with dry forages (380 vs. 357 mEq/kg; P = 0.065). Concentrations of WSC and starch were not affected (P ≥ 0.099) by slurry application or initial bale moisture, although the overall concentration of WSC in pre-ensiled HARV1 forages (7.2%) was greater than reported in other studies (Kiziksimsek et al, 2007;Schmidt et al, 2009;Kung et al, 2010), and may have been related to the drought conditions that became increasingly stressful for growing forage plants throughout the late July.…”
Section: Harv1mentioning
confidence: 50%
“…The purpose of this addition was to balance the microbial population in the material for haylage production, improving anaerobic fermentation. Approximately 1.3kg of green mass was wrapped in polyethylene bags (40 x 60cm) and vacuum sealed according to the technique described earlier (Kung Junior et al 2010). Diet composition is described in Table 1 and haylage composition is established in Table 2.…”
Section: Methodsmentioning
confidence: 99%